2016
DOI: 10.1021/acs.jpcb.6b08581
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Free-Energy Profiles of the P–O Bond Formation and Cleavage Reactions Catalyzed by DNA Polymerases β and λ

Abstract: Human X-family DNA polymerases β (Polβ) and λ (Polλ) catalyze the nucleotidyl-transfer reaction in the base excision repair pathway of the cellular DNA damage response. Using empirical valence bond and free-energy perturbation simulations, we explore the feasibility of various mechanisms for the deprotonation of the 3′-OH group of the primer DNA strand, and the subsequent formation and cleavage of P–O bonds in four Polβ, two truncated Polλ (tPolλ), and two tPolλ Loop1 mutant (tPolλΔL1) systems differing in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 95 publications
(295 reference statements)
1
18
0
Order By: Relevance
“…The catalytic Mg 2+ ion (A) clearly provides the principal linkage of the nascent RNA with the accessing NTP that is activated only upon O3′-deprotonation of the terminal nucleotide within the nascent RNA. This assumption is coherent with recent benchmark calculations of the P-O bond formation operated by DNA Polymerases β and λ 61 . Our QM/MM calculations furthermore revealed that the interactions between the NTP phosphate and other RNA molecules remained preserved, only respective bond distances varied upon altered RNA sequence (Table S5 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The catalytic Mg 2+ ion (A) clearly provides the principal linkage of the nascent RNA with the accessing NTP that is activated only upon O3′-deprotonation of the terminal nucleotide within the nascent RNA. This assumption is coherent with recent benchmark calculations of the P-O bond formation operated by DNA Polymerases β and λ 61 . Our QM/MM calculations furthermore revealed that the interactions between the NTP phosphate and other RNA molecules remained preserved, only respective bond distances varied upon altered RNA sequence (Table S5 ).…”
Section: Discussionsupporting
confidence: 89%
“…The O3′-Pα calculated with Mn 2+ for normal and O3′-deprotonated ribose of nucleotide 8 was 3.268 Å and 3.076 Å, respectively. The activated state of the RNA substrate, however, assumes O3′-deprotonation of the terminal nucleoside within the nascent RNA that takes place in the catalytic core 61 . Consequently, the majority of the QM/MM calculations employed O3′-deprotonated nucleotide 8 to illustrate the reaction state shortly before formation of the O3′-Pα phosphodiester bond.…”
Section: Resultsmentioning
confidence: 99%
“…One can attempt to compute the free energy difference between the states with either the exact or approximate expression using either Monte Carlo or MD to sample molecular configurations . The FEP method has been used to study the fidelity of DNA replication by computing the free‐energy of mismatched structures in complex with protein and for evaluation of repair pathways …”
Section: Methodsmentioning
confidence: 99%
“…[]. The EVB method was used to study the synthesis of DNA during replication and base excision repair of DNA damage . The EVB method is much less computationally demanding than the conventional ab initio QM/MM method and is able to faithfully describe catalytic effects and enzyme–solvent interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation